57‐5: Invited Paper: Excimer Laser Annealing and Spot‐Beam Crystallization of Si Films for Advanced Displays. Issue 1 (30th May 2018) - Im, James S.; Song, Ruobing; Wong, Vernon K.; Pan, Wenkai; Choi, Insung; Yu, Miao
Abstract : This paper discusses recent laser‐crystallization‐related research results and advances that are enabling us to: (1) gain an in‐depth understanding of the ELA method currently utilized in the industry, and (2) suggest that a quasi‐CW fiber‐laser‐based SBC technique can be developed into a viable laser annealing method.